DESAIN TATA KELOLA REKAM MEDIS BERBASIS ELEKTRONIK TERHADAP KUNJUNGAN PASIEN RAWAT JALAN DAN OBAT - Bunga Efendi; Rizki Nurarif Faturrahman; Falaah Abdussalaam; Irda Sari (JURNAL ILMIAH BETRIK, 2023)
The community health centers are primary health care facilities to serve patients. Patient services at the Lembang comunity health center that could benevit from improvement, one of which is in the process of examining data on outpatient visits and medications, currently the system is manual, but the manual system causes delay in patient processing and data reporting. These delays can be fixed by updating form the current use of Microsoft Word and Microsoft Excel, it will take a long time because the data has to be processed first. The purpose of this research is to help the officers make it easier to check outpatient data, medication data and generate reports. Based on the analyzing of existing problems, a conclusion can be drawn that his new update design of the outpatient visits and medical system will help to create and easier way for officers to accurately chech data records and develpo detailed reports. In addition to creating an easier process, data will become more secure under the new system because it will not be accessible to the public.